The South African position regarding when a legal duty may be placed upon a person - Seedat, Wazeer (The IIE, 2022)
This study will focus on whether persons within the Republic of South Africa would be obliged to act positively to prevent harm/damage from falling onto another person within the context of wrongfulness in delict. According to Neethling and Potgieter Potgieter,1 a positive act is where a person fails to take precautions against the occurrence of damages, and this failure to act is not an integral aspect of positive conduct. Examples of a positive act include: a homeowner who does not exercise control of a fire which has broken out in their home without the person’s doing; a police officer who fails to protect someone who is being assaulted by a third party; the police who fail to stop an inmate from escaping and that inmate then assaults an innocent third party. With respect to the concept of a legal duty, Van der Merwe and Oliver,2 outlines the concept of a legal duty as it pertains to the infringement of a subjective right, which correlates with a legal duty imposed on another person to not infringe upon that subjective right. Concepts such as legal duty and positive performance will be broken down in detail to understand what these terms entail, and how they are utilised by South African courts when making decisions. These are two concepts which fall within the law of delict which is a sphere within private law and protects against the infringement of private interests.
Keywords: Legal duty